PELAKSANAAN PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SMP NEGERI 1 KECAMATAN SINTANG KABUPATEN SINTANG - Robertus Sirang Framita E01107109 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article raised school implementation grand program for the development of education in SMPN 1 in the district of Sintang. Approach used is qualitative approach. Results of research conducted to explain the coordination between the school has a process of communication that is not good, causing inter BOS fund trustees do not run smoothly. The socialization provided by the school education department is only in outline that school  resulted in the lack of understanding about the use of BOS funds that the rules are so complex, this causes the school to make its own policy into practice resulted in the allocation of funds that are not well targeted. Monitoring conducted by the BOS management team either from central or provincial governments have done several times, and evaluate programs that have been implemented, but there are still problems that occur in practice. It is also human resources that have not been so skilled in managing BOS. This is evident by the still existing supporting facilities inadequate educational facilities and that have been damaged but not repaired. Though the mild improvement schools for education facilities are listed in RKAS (School Work Plan and Budget). The attitude of the implementers do not have the same view in an effort to succeed in the implementation of programs that lead the implementers did not cooperate with the optimal policy and cause problems when implementing policies.Keywords: BOS program implementation, allocation of funds, collaboration in decision-making, and stakeholder attitudes.